Technique and traditional knowledge in the professional graduation of the Technologist in Civil Construction (Research, Society and Development, 2021)
Seeking to better understand the historical relationship of the human being with the technique, and going beyond the dichotomy that suggests the pair theory and practice in the scope of education, this article seeks to bring, through the thought of the French philosopher Gilbert Simondon and the educator Jarbas Novelino Barato, each in its own context, reflections on the teaching and learning process in professional and technological education courses. This is a bibliographic and documentary research that seeks to discuss the relevance and contributions of traditional knowledge in the trajectory of building the profile of professional Technologists, in turn directly linked to culture and contemporary thought. The focus of this research is centered on the study of documents related to Civil Construction Technology courses and on the analysis of the training of these professionals. Therefore, it is intended to conceptualize the highlighted terms and relate them to concrete aspects of the type of course in question.